2013
DOI: 10.1016/j.ijhydene.2012.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Progress of international hydrogen production network for the thermochemical Cu–Cl cycle

Abstract: This paper presents recent advances by an international team which is developing the thermochemical copperchlorine (Cu-Cl) cycle for hydrogen production. Development of the Cu-Cl cycle has been pursued by several countries within the framework of the Generation IV International Forum (GIF) for hydrogen production with the next generation of nuclear reactors. Due to its lower temperature requirements in comparison with other thermochemical cycles, the Cu-Cl cycle is particularly well matched with Canada's Gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 45 publications
(21 reference statements)
0
26
0
Order By: Relevance
“…The large difference in Cu I bulk concentrations in combination with the observed high current densities and limiting currents suggested that this species was a likely candidate as an electrochemically active species. Given the high concentrations of CuCl 3 2− (aq) and CuCl 3 − (aq) from thermodynamic speciation calculations, Equation 3 is the simplest form of a possible anode reaction, written in its reduction form:…”
Section: Resultsmentioning
confidence: 99%
“…The large difference in Cu I bulk concentrations in combination with the observed high current densities and limiting currents suggested that this species was a likely candidate as an electrochemically active species. Given the high concentrations of CuCl 3 2− (aq) and CuCl 3 − (aq) from thermodynamic speciation calculations, Equation 3 is the simplest form of a possible anode reaction, written in its reduction form:…”
Section: Resultsmentioning
confidence: 99%
“…In the Cu-Cl cycle, water is decomposed into hydrogen and oxygen through intermediate Cu-Cl compounds [1,2]. Nuclear-based ''water splitting'' requires an intermediate heat exchanger between the nuclear reactor and hydrogen plant, which transfers heat from the reactor coolant to the thermochemical cycle.…”
Section: Thermochemical Hydrogen Production Cyclementioning
confidence: 99%
“…The dilute gas dynamic viscosity for CLS model is written as [2,3,[14][15][16][17][18][19][20][21][22][23]:…”
Section: Thermodynamic and Transport Properties Of Statementioning
confidence: 99%
See 2 more Smart Citations